Searching for new directions for energy policy: Testing the cross-effect of risk perception and cyberspace factors on online/offline opposition to nuclear energy in South Korea - Wang, Jaesun; Kim, Seoyong (Sustainability (Switzerland), 2019)
In the internet age, a considerable amount of information about risk events and objects is shared in cyberspace. Since online and offline spaces are not discrete, there is a cross-effect in which perceptual or attitudinal factors in cyberspace influence offline actions, while offline attitudes affect online actions. However, few studies have examined this cross-effect. In the present study, the intention to engage in online or offline behaviors opposing nuclear energy was the dependent variable. The independent variables included risk perception factors (i.e., perceived risk, perceived benefit, trust, knowledge, and stigma) in the risk perception paradigm, and cyber factors (i.e., self-efficacy in cyberspace, involvement on the internet, trust in cyberspace, conformity to online opinion, and belief in online rumors) in the cyberpsychology paradigm. Our findings offer evidence for the cross-effect of online or offline predictors on online/offline behaviors opposing nuclear energy. All the variables in the cyberspace paradigm influenced offline opposition, while those in the risk perception paradigm affected online opposition. Moreover, the five online-related risk perception variables played a significant role in moderating the relationships of predictors in the risk perception paradigm with offline opposition.
Keywords: Acceptance of nuclear power; Cyberpsychology; Risk perception; Risk perception paradigm